Hubungan Persepsi dan Preferensi Atasbagi Hasil Pembiayaan Mudharabah Musytarakah terhadap Minat Menjadi Peserta Asuransi Syariah - Marianti Meha; Muhammad Ramadhan; Juliana Nasution (ManBiz: Journal of Management and Business, 2023)
Insurance is a way or method to maintain humans in avoiding risks, various dangers that will occur in their lives, in the course of their life activities or in their economic activities. Sharia insurance is a business that protects and helps each other between several parties through investments in the form of assets or tabarru' which provides a pattern of returns used to deal with certain risks through contracts in accordance with sharia principles. This study aims to determine the relationship between perceptions and preferences of the profit sharing of mudharabah financing on the interest in becoming participants in sharia insurance for high school teachers of the Smart Pure Islamic Education Foundation, either partially or simultaneously. The method used in this study is a quantitative method. The population of this study was conducted on teachers in one high school in Medan, North Sumatra with a sample of 65 teachers. Using primary data and distributing questionnaires and multiple regression analysis methods using hypothesis testing. The results of this study simultaneously from the variables of perception and preference for mudharahmusytarakah financing have a significant effect on interest. then partially perception and preference variables affect the interest in becoming a participant of sharia insurance. Keywords: Perception, Preference, Interest, MudharabahMusytarakah, Sharia Insurance